THE EFFECT OF PERCEIVED EASE OF USE ON INTENTION TO USE ON BANK SYARIAH INDONESIA MOBILE BANKING USERS IS MEDIATED BY E-TRUST AND RELIGIOSITY AS MODERATORS - Dennis Shabri Alfani; Agung Yuniarto M.S; Radityo Putro Handrito (CV. Radja Publika, 2023)
The increase in smartphone users has driven customer demand for mobile banking services, so that many banks have offered innovative banking services to expand the reach of their customers who have accounts or those who do not have bank accounts. Banking is developing the use of mobile banking as a demand to meet the increasing transaction needs of individuals and companies. This is supported by advances in technology, especially cellular telecommunication. Research on